2013
DOI: 10.1080/10409289.2013.744682
|View full text |Cite
|
Sign up to set email alerts
|

Effortful Control, Behavior Problems, and Peer Relations: What Predicts Academic Adjustment in Kindergartners from Low-Income Families?

Abstract: This study examined the role of effortful control, behavior problems, and peer relations in the academic adjustment of 74 kindergarten children from primarily low-income families using a short-term longitudinal design. Teachers completed standardized measures of children’s effortful control, internalizing and externalizing problems, school readiness, and academic skills. Children participated in a sociometric interview to assess peer relations. Research Findings: Correlational analyses indicate that children’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 76 publications
2
26
0
Order By: Relevance
“…Children's effortful control also significantly predicted school readiness scores on the DRDP index, with children rated as having higher effortful control abilities also scoring higher on the DRDP index. This is also consistent with previous research considering effortful control as a predictor of multiple measures of school readiness (Morris et al, 2013;Thompson et al, 2013;Son et al, 2013;Valiente et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Children's effortful control also significantly predicted school readiness scores on the DRDP index, with children rated as having higher effortful control abilities also scoring higher on the DRDP index. This is also consistent with previous research considering effortful control as a predictor of multiple measures of school readiness (Morris et al, 2013;Thompson et al, 2013;Son et al, 2013;Valiente et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…For children with lower effortful control abilities, engagement in academic tasks may be more difficult and have a subsequent effect on learning. Early effortful control measures have been linked with both concurrent academic achievement in the form of school readiness as well as later academic achievement longitudinally (Morris et al, 2013;Thompson et al, 2013;Son, Lee, & Sung, 2013;Valiente et al, 2013). Based on this research, we also examine effortful control as a predictor of our school readiness index.…”
Section: Predictors Of School Readiness: Parenting and Effortful Controlmentioning
confidence: 99%
“…In general, further study examining the interplay between social withdrawal and reading may also benefit from a more nuanced examination of the pathways through which the predictive relationship travels. Specifically, research on low‐income kindergarten students has demonstrated that effortful control has had an indirect effect on school readiness through internalizing, but not externalizing, symptoms (Morris et al., ). The present study did not include explicit measures of effortful control, but it stands to reason that effortful control, classroom participation, attention, and school liking may all be avenues for exploration as potential mediators of the association between social withdrawal and attenuated academic learning.…”
Section: Discussionmentioning
confidence: 99%
“…For example, preschoolers' behavioral regulation (assessed with the Head-Toes-Knees-Shoulders task which requires attention, working memory, and inhibiting dominant responses to perform a non-dominant demand; Diamond, 2002) predicted concurrent academic achievement, controlling for earlier levels of achievement and behavioral regulation (McClelland et al, 2007). There is also some longitudinal evidence for the association between effortful control (e.g., assessed with a variety of behavioral measures of inhibitory control and set shifting) and academic achievement (Clark, Pritchard, & Woodward, 2010; McClelland et al, 2014; Morris et al, 2013; Ponitz et al, 2009), although the use of control variables across studies has been inconsistent. For example, effortful control (measured with behavioral and adults' reports of inhibitory control and attentional focusing/shifting) in kindergarten positively predicted math and reading achievement in kindergarten or second grade (Cerda, Im, & Hughes, 2014; Valiente, Lemery-Chalfant, & Swanson, 2010), controlling for background variables (e.g., socioeconomic status [SES]) but not prior academic achievement.…”
Section: Relations Between Children's Effortful Control and Academic mentioning
confidence: 99%